Too Late, Too Soon Olga Spessivtseva - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Olga Spessivtseva. It seems wrong that Spessivtseva should be remembered more for what happened to her than for what she did. Diaghilev was hungry for dancers and the Maryinsky Theatre was his preferred feeding-station. PALABRAS CLAVE: Olga Spessivtseva, life and career.